Investigation on determinants of financial management behavior among employees in Melaka, Malaysia / Hazrel Moktar and Nur Syafiqah Husna Mohd Sazalli - Moktar, Hazrel; Mohd Sazalli, Nur Syafiqah Husna (Faculty of Business and Management, 2019)
This research is to investigate the relationships between financial attitude, financial self-efficacy, financial literacy with financial management behavior. The sample in this research is to investigates employees in Melaka, Malaysia which involved 216 totals of respondents were chosen through purposive sampling of employees that working in UiTM Kampus Bandaraya Melaka and Sun Power Malaysia. In order to obtain the result, frequency distribution, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis were conducted in the analysis part. The findings recommend that the financial attitude, financial self-efficacy and financial literacy has significant relationships with financial management behavior. Financial literacy is found as the most influenced predictor towards financial management behavior followed by financial self-efficacy and financial attitude. These finding could contribute to the body of knowledge by identifying determinants of financial management behavior among employees in Melaka. Social cognitive theory and theory of planned behavior is used to underpin a proposed theoretical framework. The study shows the absence of financial attitude, financial self-efficacy and financial literacy will enhance the level of financial management behavior among employees in Melaka.